Peer social support and academic adaptation among new nursing students - Arfiansyah, Muhamad Riffo; Rokhmah, Noor Ariyani; Imallah, Rosiana Nur (JOURNAL OF Mental Health Concerns, 2026)
Background: New students experience a transition period to university life that requires academic, social, and emotional adaptation. Students in the Bachelor of Nursing and Professional Nurse Program face more complex adaptation demands due to high academic workloads. Peer social support is considered to play an important role in helping new students adjust to the university environment. Purpose: To determine the relationship between peer social support and the adaptation of new students. Method: A quantitative approach with a descriptive correlational design and a cross-sectional method. The research population consisted of all new students of the Bachelor of Nursing and Professional Nurse Program at ‘Aisyiyah University Yogyakarta in the 2025/2026 academic year, totaling 233 students. A sample of 77 respondents was selected using random sampling. Data were collected using a peer social support questionnaire and the Student Adaptation to College Questionnaire (SACQ). Data analysis was conducted using Kendall’s Tau test. Results: The results of Kendall’s Tau statistical test showed a p-value of p = 0,390 (p > 0.05) with a correlation coefficient of -0.097. These findings indicate that there is no significant relationship between peer social support and the adaptation of new students. The correlation coefficient shows a very weak relationship with a negative direction. Conclusion: Based on the results of the study, it can be concluded that peer social support has no significant relationship with the adaptation of new students. However, peer social support remains important as a supporting factor in the adjustment process of new students in the university environment. Keywords: New Student Adaptation; Peer Social Support; Transition Period.